Acoustic radiation force impulse elastography: a tool for muscle aging assessment: a pilot study. Issue 2 (4th May 2021) - Regueme, Sophie C.; Frulio, Nora; Trillaud, Hervé; Laurent, Christophe; Rullier, Eric; Dallaudière, Benjamin; Bourdel‐Marchasson, Isabelle
Abstract: Background: CAPARFI study explored whether sonoelastographic data collected using the acoustic radiation force impulse (ARFI) system are reliable when evaluating skeletal muscles and whether the technique can detect muscle changes with aging. Methods: Twenty young (YH; 18–30 years) and 30 old (OH; ≥70 years) healthy volunteers and 15 old patients with cancer (OP; ≥70 years) were assessed through quantitative ARFI measurements (m s −1 ) of the relaxed rectus femoris, tibialis anterior, and soleus muscles, and Short Physical Performance Battery (SPPB) test. The reliability in ARFI measurements was evaluated by intra‐class correlation coefficient. Among‐group differences in ARFI measurements and SPPB were evaluated using a global linear model. Results: Acoustic radiation force impulse measurements demonstrated high reliability in all groups (intra‐class correlation coefficient > 0.82). ARFI measurements of the rectus femoris muscle were significantly lower in both the OH and OP groups than in the YH group (1.46 ± 0.12 and 1.50 ± 0.32 vs. 1.80 ± 0.35 m s −1 ). The ARFI measurements of the soleus muscle were significantly lower in the OP group than in the YH group (1.37 ± 0.37 vs. 1.70 ± 0.53 m s −1 ). No significant difference was observed for tibialis anterior muscle. Significantly lower SPPB scores were observed in the OP group (10.3 ± 1.4 out of 12) than in the YH (12.0 ± 0.0) and OH groups (11.5 ± 1.0). Conclusions: This study demonstrated that ARFI quantitative measurements are reliable in relaxed skeletal muscle and may be reliably used to explore muscle changes with aging and/or neoplasia in clinical practice.